2015
DOI: 10.1002/lary.25708
|View full text |Cite
|
Sign up to set email alerts
|

Disease homogeneity and treatment heterogeneity in idiopathic subglottic stenosis

Abstract: Objectives/Hypothesis: Idiopathic subglottic stenosis (iSGS) is a rare and potentially life-threatening disease marked by recurrent and progressive airway obstruction frequently requiring repeated surgery to stabilize the airway. Unknown etiology and low disease prevalence have limited the ability to characterize the natural history of iSGS and resulted in variability in surgical management. It is uncertain how this variation relates to clinical outcomes. Study Design: Medical record abstraction. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
281
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(299 citation statements)
references
References 20 publications
14
281
2
2
Order By: Relevance
“…As in other studies [13, 8, 1114], this study demonstrated homogeneity among ISS patients, who were mainly healthy females of European descent, diagnosed in their 50 s and requiring multiple procedures. The pathophysiology of the condition is unclear, but the age at diagnosis of approximately 50 years coincides with onset of menopause, supporting the hypothesis that hormones influence the etiologic process [1, 4, 11, 15].…”
Section: Discussionsupporting
confidence: 86%
“…As in other studies [13, 8, 1114], this study demonstrated homogeneity among ISS patients, who were mainly healthy females of European descent, diagnosed in their 50 s and requiring multiple procedures. The pathophysiology of the condition is unclear, but the age at diagnosis of approximately 50 years coincides with onset of menopause, supporting the hypothesis that hormones influence the etiologic process [1, 4, 11, 15].…”
Section: Discussionsupporting
confidence: 86%
“…Regardless of etiology, the treatment goals center around creating an open and lasting airway and are accomplished surgically. Despite the relative homogeneity of the disease presentation and population, the treatment of iSGS remains quite variable on a spectrum from endoscopic management with balloon dilation to cricotracheal resection (CTR) . Despite CTR having less recurrence than endoscopic management, there can be significant morbidity associated with undergoing the open procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Such a rare disease has proven difficult to ascertain meaningful answers to research questions in the past. Recently, the North American Airway Collaborative (NoAAC) established a multi‐institutional collection of data for iSGS to help elucidate answers . Interestingly, there is significant institutional variability with treatment choice and criteria for selecting patients to undergo CTR versus endoscopic excision with balloon dilation .…”
Section: Introductionmentioning
confidence: 99%
“…An intense episode of coughing, the presence of mycobacterial infections, and gastroesophageal reflux (GERD) laryngitis in fact have been proposed as possible triggers . Although presence of such purported triggers is inconstant, the prevalence of clinical GERD in the IPSS series has been reported to be similar to the one of the general population . Yet, the presence of pepsin was identified in the larynx of nearly two‐thirds of a further series .…”
Section: Introductionmentioning
confidence: 99%